Radiological and Toxicity Hazards Estimate of Drinking Water in Al-Diwaniyah, Iraq - Abbas, M. A.; Hammood, H. A.; Salman, D. J. (Atom Indonesia, 2024)
In this work, analyses of 222Rn concentration and effective 226Ra content in all available types of drinking water in Al-Diwaniyah city, Iraq, were achieved by using CR-39 detectors technique. The annual effective dose from 222Rn and 226Ra distribution by three age groups were calculated. Radiological and chemical hazards were also calculated in drinking water samples. Drinking water samples were taken from tap water, water treatment plants, reverse osmosis water, and bottled drinking water in Al-Diwaniyah city. Effective 226Ra content level in some tap water samples were bigger than recommended value WHO for drinking water (1 Bq/L), but far below maximum acceptable limit of 370 Bq/L according to IAEA. All other values of 222Rn concentration and effective 226Ra content, annual effective dose, cancer morbidity and mortality hazards, and the lifetime average daily dose caused by consumption 226Ra in drinking water were less than recommended limits. Therefore, 222Rn concentration and effective 226Ra content in drinking water obtained in this work cannot give rise to radiological and chemical threats to population. However, for greater safety, we advise not to use tap water directly as drinking water. This work will provide important new data on the possible health effects of drinking water in Al-Diwaniya city.